Deployment and reallocation in mobile survivability-heterogeneous wireless sensor networks for barrier coverage - Tian, Jie; Liang, Xiaoyuan; Wang, Guiling (Ad hoc networks, 2016)
Barrier coverage is a widely adopted coverage model for intruder surveillance application in wireless sensor networks. However, when sensor nodes are deployed outdoors, they are subject to environmental detriments and will be failed while operating in the rain. Thus, one barrier is not robust to provide barrier coverage under both sunny and rainy weather. In this paper, we study the barrier coverage problem in a mobile survivability-heterogeneous wireless sensor network, which is composed of sensor nodes with environmental survivabilities to make them robust to environmental conditions and with motion capabilities to repair the barrier when sensors are dead. Our goal is to keep field to be monitored continuously under both sunny and rainy weather and to prolong the network lifetime as much as possible. We propose a novel greedy barrier construction algorithm to solve the problem. The algorithm adopts weather forecast to direct the barrier construction under sunny and rainy weather, and the energy consumption of construction is minimized. Simulation results show that our algorithm efficiently solves the problem and outperforms other alternatives.